Барочная живопись как источник идентификации и атрибуции культурных ценностей - Пуларии, Т.В. (Культура народов Причерноморья, 2013)
Статья посвящена выявлению атрибутивных признаков старинных музыкальных
инструментов, изображенных на картинах западноевропейских художников эпохи барокко, как
возможного способа таможенной идентификации культурных ценностей, являющихся предметом
коллекционирования, с целью предотвращения их незаконного перемещения через таможенную границу
Украины. Отдельно рассматриваются эволюционирующие формы клавишно-щипковых струнных
инструментов – спинет и вёрджинел – как наиболее близкие по времени использования и по некоторым
музыкальным характеристикам разновидности клавесина.
Ключевые слова: атрибуция и таможенная идентификация культурных ценностей, барочная
живопись, барочные музыкальные инструменты, музыкальная иконография Стаття присвячена виявленню атрибутивних ознак старовинних музичних інструментів,
зображених на картинах західноєвропейських художників барокової доби, як можливого засобу митної
ідентифікації культурних цінностей, що є предметом колекціонування, з метою запобігання їх
незаконного переміщення через митний кордон України. Окремо розглядаються еволюціонуючі форми
клавішно-щипкових струнних інструментів – спінет і вьорджінел – як найбільш близькі за часом
використання і за деякими музичними характеристиками різновиди клавесину.
Ключові слова: атрибуція та митна ідентифікація культурних цінностей, бароковий живопис, барочні
музичні інструменти, музична іконографія The article is devoted to revelation of attributive signs of Ancient Musical Instruments depicted in
paintings by Western European Artists of the Baroque period as a possible means of Customs Identification of
Cultural Property that are the collectible in order to prevent their illegal movement across the Ukraine customs
border. Evolving forms of keyboard-plucked string instruments – Spinet and Virginal – are considered
separately as the kinds of Harpsichord are closest in time use and for some musical characteristics. The design
and decor of rare musical instruments the Flemish school of Bos, Ruckers, Couchet are studied in the paintings
of Michelangelo Merisi da Caravaggio, Lavinia Fontana, Johannes Vermeer, Gabriel Metsu, Godaert Camper,
Jan Miense Molenaer, Martin Pepeyn. Features of instruments of Ruckers – the dynastic corporation Flemish
masters producing harpsichords at the end of the XVI and XVII centuries are discovered on the famous
canvases, such as deca is decorated by blue arabesques on the periphery and flower ornament in the central
outlet made of gold-plated tin sometimes with birds, insects, fruits, vegetables, bonded on both sides with stylized
initials, etc. Baroque paintings reproduces different in size and shape types of popular musical instruments: a
portable triangular Spinet, rectangular Virginal in the form of boxes for needlework, decorated with gilded
carvings, incrustation, moralistic inscriptions in Latin, and so on.
Keywords: аttribution and Customs Identification of Cultural Property, Baroque Art, Baroque Musical
Instruments, Musical Iconography